A Three-Arm Parallel-group Exploratory Trial documents balance improvement without much evidence of white matter integrity changes in people with multiple sclerosis following two months ambulatory neuroproprioceptive "facilitation and inhibition" physical therapy - Řasová, Kamila; Bučková, Barbora; Prokopiusová, Terezie; Procházková, Marie; Angel, Gabriela; Marková, Magdaléna; Hrušková, Natália; Štětkářová, Ivana; Špaňhelová, Šárka; Mareš, Jan; Tintěra, Jaroslav; Zach, Petr; et al. (European Journal of Physical and Rehabilitation Medicine, 2021)
BACKGROUND: Changes of white matter integrity in people with multiple sclerosis (MS) were documented following mainly motor/skill acquisitions physical therapy, while following neuroproprioceptive "facilitation, inhibition" (neurofacilitation) only by two pilot studies. Neurofacilitation has potential to induce white matter changes due to the possibility of interfering with the neuronal tactility threshold. However stronger evidence is missing. AIM: This study investigates whether neurofacilitation (three physical therapy types) induce white matter changes and if they relate to clinical improvement. DESIGN: The Three-Arm Parallel-group Exploratory Trial (NCT04355663). SETTING: Each group underwent different kinds of two months ambulatory therapy (Motor Program Activating Therapy, Vojta's reflex locomotion and Functional Electric Stimulation in Posturally Corrected Position). POPULATION: MS people with moderate disability. METHODS: At baseline and after the program, participants underwent magnetic resonance diffusion tensor imaging (DTI) and clinical assessment. Fractional anisotropy maps obtained from DTI were further analyzed using tract-based spatial statistic exploring the mean values in the whole statistic skeleton. Moreover, additional exploratory analysis in 48 regions of white matter was done. RESULTS: Ninety-two people were recruited. DTI data from 61 people were analyzed. The neurofacilitation (irrespective type of therapy) resulted in significant improvement on the Berg Balance Scale (P=0.0089), mainly driven by the Motor Program Activating Therapy. No statistically significant change in the whole statistic skeleton was observed (only a trend for decrement of fractional anisotropy after Vojta's reflex locomotion). Additional exploratory analysis confirmed significant decrement of fractional anisotropy in the right anterior corona radiata. CONCLUSIONS: Neurofacilitation improved balance without much evidence of white matter integrity changes in people with MS. CLINICAL REHABILITATION IMPACT: The study results point to the importance of neuroproprioceptive "facilitation and inhibition" physical therapy in the management of balance in people with multiple sclerosis; and the potential to induce white matter changes due to the possibility of interfering with the neuronal tactility threshold.
Keywords: White Matter; techniky fyzikální terapie; lidé; Diffusion Tensor Imaging; bílá hmota; Humans; roztroušená skleróza; Multiple Sclerosis; Physical Therapy Modalities; zobrazování difuzních tenzorů